ANALISIS PERENCANAAN PEMBELAJARAN SEBAGAI UPAYA MENINGKATKAN EFEKTIFITAS DALAM PROSES BELAJAR MENGAJAR DI SD INPRES ALEMBA - Frits Donasius Kamengmau; Yessy Mata (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to analyze lesson planning as an effort to improve the effectiveness of the teaching and learning process at SD Inpres Alemba. The research uses a qualitative approach with a descriptive research type. The research subjects consist of the principal and teachers, while data collection techniques are carried out through observation, interviews, and documentation. The data are analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and drawing conclusions. Research results show that teachers have prepared lesson plans that include learning objectives, teaching materials, methods, media, and assessments in accordance with the applicable curriculum. Lesson planning helps teachers carry out the teaching and learning process more effectively, increases student engagement, and makes it easier to achieve learning goals. Although there are still challenges such as limited learning media, differences in students' abilities, and time constraints, teachers try to overcome them by adjusting their teaching strategies. In this way, systematically prepared lesson plans contribute positively to improving the effectiveness of the teaching and learning process at SD Inpres Alemba.